Efficacy of the device combining high-frequency transcutaneous electrical nerve stimulation and thermotherapy for relieving primary dysmenorrhea: a randomized, single-blind, placebo-controlled trial. (November 2015) - Lee, Banghyun; Hong, Seung Hwa; Kim, Kidong; Kang, Wee Chang; No, Jae Hong; Lee, Jung Ryeol; Jee, Byung Chul; Yang, Eun Joo; Cha, Eun-Jong; Kim, Yong Beom
Abstract: Objective: To investigate the efficacy and safety of the combined therapy with high-frequency transcutaneous electrical nerve stimulation (hf-TENS) and thermotherapy in relieving primary dysmenorrheal pain. Study design: In this randomized, single-blind, placebo-controlled study, 115 women with moderate or severe primary dysmenorrhea were assigned to the study or control group at a ratio of 1:1. Subjects in the study group used an integrated hf-TENS/thermotherapy device, whereas control subjects used a sham device. A visual analog scale was used to measure pain intensity. Variables related to pain relief, including reduction rate of dysmenorrheal score, were compared between the groups. Results: The dysmenorrheal score was significantly reduced in the study group compared to the control group following the use of the devices. The duration of pain relief was significantly increased in the study group compared to the control group. There were no differences between the groups in the brief pain inventory scores, numbers of ibuprofen tablets taken orally, and World Health Organization quality of life-BREF scores. No adverse events were observed related to the use of the study device. Conclusions: The combination of hf-TENS and thermotherapy was effective in relieving acute pain in women with moderate or severe primary dysmenorrhea.